A Bahasa Malaysia interactive book app as a speech-language therapy tool for children with language delay - Bao, Xin Gang; Suhaila Zainudin,; Hasherah Mohd Ibrahim,; Lam, Meng Chun (Penerbit Universiti Kebangsaan Malaysia, 2017)
Interactive story books (ISB) mobile application is defined as an app for children to practice their speech, language and literacy skills. Information has shown that ISB can be used to support education and learning for individuals with language delay. In general, visual and auditory artifacts are included in this kind of app which makes the app an incredible aid to facilitate speech and language skills. Considering the situation in Malaysia, many of the developed ISB suffers from a lack of practical experience with children, especially for the children who have language delay. The evidence can be seen from the lack of apps for the children whose first language is Bahasa Malaysia. Malaysian children with language delay and their parents are the subjects in this research. The children and their parents were asked to answer a survey about the ISB requirement. The survey focused on collecting the requirement for the ISB targeted for children with language delay. The survey data were analyzed to get the requirements for the app. Based on the requirements, the ISB can be developed using the Android platform. The main finding of the study is the practical requirements of ISB in Bahasa Malaysia for children with language delay in collaboration with Speech and Language Pathologists (SLPs), parents and children.